Under Her Hat: Glimpses of Bonnet View - Tomić, Janica (Zagadnienia Rodzajów Literackich, 2020)
The paper introduces the concept of tableau as articulated by film history and theory, with examples from the films of Roy Andersson, Jean-Luc Godard and Lars von Trier. A lesser known tradition, the bonnet view originates from Kelly Reichardt’s western Meek’s Cutoff which set out to tell the story from “the point of view of the woman who pours John Wayne’s coffee.” By replacing generic conventions, notably the customary widescreen with a square-like image, Meek’s Cutoff conveys the visual and social restrictions signified by women’s bonnets. The bonnet view is further traced in the tableaus of TV-series Handmaid’s Tale and other cinematic portrayals of women’s history ( Jessica Hausner’s Amor Fou and Carl Th. Dreyer’s The Day of Wrath), exploring its potential as a vehicle of the female gaze.